Dust and Molecule Formation and Processing in Supernovae and their Remnants. (5th March 2015) - Rho, J.; Andersen, M.; Tappe, A.; Gomez, H.; Smith, M.; Bernard, J. P.; Onaka, T.; Cami, J.
Abstract: Supernovae (SNe) produce, fragment and destroy dust, molecules and nucleosynthetic elements, and reshape and modify the ISM. I will review recent infrared observations of supernova remnants (SNRs) and SNe which show that SNe are important sites of dust and molecule formation and are major dust creators in the Universe. Detection of carbon monoxide (CO) fundamental band from the young SNR Cas A indicates that astrochemical processes in SNRs interacting with molecular clouds provide astrophysical laboratories to study evolution of the ISM returning material from dense clouds into the more diffuse medium and galactic halo. Two dozen SNRs are known to be interacting with molecular clouds using H2 and millimeter observations. Recent Spitzer, Herschel and SOFIA observations along with ground-based observations have greatly advanced our understanding shock processing and astrochemistry of dust, H2, high J CO, and other neutral and ionized molecules and polycyclic aromatic hydrocarbon (PAH). Ionized molecules and warm layer of molecules that are excited by UV radiation, X-rays, or cosmic rays will be described. Finally I will discuss how astrochemical processes of dust and molecules in SNRs impact the large scale structures in the ISM.